Maisy makes gingerbread: maisy story book - Cousins, Lucy (Walker London, 2011)
"Maisy Makes Gingerbread" by Lucy Cousins is a charming children's story featuring Maisy the Mouse as she embarks on a delightful adventure in baking. In this sweet tale, Maisy decides to make gingerbread cookies and gathers her friends to join in the fun. The book follows their process of mixing ingredients, rolling out the dough, and baking the cookies, all illustrated with bright, engaging artwork.